CHILD-FRIENDLY DIGITAL LITERACY MEDIA TRAINING FOR ENGLISH LEARNING IN ELEMENTARY SCHOOLS - Nuroh, Ermawati Zulikhatin; Liansari, Vevy (Journal of Social Comunity Services, 2026)
Objective : This article reports on a community service program aimed at enhancing the creativity and digital literacy of elementary school English teachers through the integration of child-friendly digital media. Method : The program, implemented in collaboration with elementary school English teachers in Sidoarjo, involved 23 elementary school English teachers who participated in hands-on training using Canva, Wordwall, and AI to create digital media aligned with their teaching objectives. The training program employed a mixed-method quantitative approach, combining observations, surveys, and qualitative feedback to explore teacher engagement, digital media, and classroom implementation. Results : The results of this community service program demonstrated the significant potential of child-friendly digital English media to enhance teaching creativity among elementary school English teachers. By integrating technology-based media, such as Canva, Wordwall, and AI into their teaching practices, the 23 participating teachers were able to expand their pedagogical repertoire and begin shifting from conventional approaches to more innovative, interactive, and student-centered ones. Although challenges, particularly time constraints, limited the full implementation of the developed materials, the teachers' increased digital literacy and willingness to explore new methods are promising indicators of professional growth. Novelty : The results of this community service program demonstrated the significant potential of child-friendly digital English media to enhance teaching creativity among elementary school English teachers.